Atomistic simulation of EELS of SiON/Si interface and SiON breakdown - Wang, Zhongrui. (2009)
Electron Energy Loss Spectroscopy (EELS) is the statistical observation of energy loss of the emitted electrons from Transmission Electron Microscope (TEM). The electron beam undergoes a many-body scattering process with nucleus and electrons of the specimen. The electrons energy loss spectrum which is obtained from electron spectroscopy consists of two regions corresponding to different scattering mechanisms. The low loss part with energy ranges from 0 electronic volts to 50 electronic volts is caused by surface and bulk plasmon oscillations which are highly sensitive to the dielectric properties of the material as well as the geometry of the specimen. The spectrum for 1-Dimensional dielectric stack with parallel incident TEM electrons was calculated by employing the classical electrodynamics Hertz potential vector approach. An analytic solution of the Hertz potential vector for arbitrary 1-Dimensional geometry has been obtained to simulate and interpret the Si/SiOx spectrum under the influence of thickness of central oxide region, thickness of the side Si region as well as the interaction of surface plasmons. Based on the same strategy of solving 1-Dimensional spectrum problem, the solution to the Maxwell’s equations for an equilateral triangular dielectric nanowire has been developed employing the Green’s function approach. The corresponding eigenfunctions are obtained by using the standing wave conditions. Both 1-Dimensional and 2-Dimensional simulation results have been compared with the existing experimental work and it shows excellent agreement with high sensitivity to dielectric material properties.